Grow out Carp Polyculture by Women : A Case Study from Odisha - De, H. K.; Chattopadhyay, D. N.; Radheyshyam,; Saha, G. S.; Dash, A. K.; Satpati , T. S.; Pal , S. (Indian Journal of Extension Education, 2013)
Women are reported to be involved in aquaculture in variety of ways and contribute substantially in aquaculture  development. Aquaculture as a weapon to fight malnutrition and poverty has been recognized in many parts of the world.  In India too, both government and non-government organizations are giving adequate emphasis to promote aquaculture  among resource poor women. Jay Hanuman women self help group (SHG) in Boudh district of Odisha, India is one such  successful case of empowering women through aquaculture. The group has taken lease of a community tank 'Kaliabundh'  measuring 1 ha and started practicing grow out carp polyculture. In 2010-11, the group has harvested 1232 kg/ha fish  (Catla catla, Labeo rohita, Cirrhinus mrigala, Cyprinus carpio and Ctenopharyngodon idella) from that pond which used  to yield 700 kg/ha fish earlier. Central Institute of Freshwater Aquaculture (CIFA) located at Bhubaneswar, India imparted  hands on training and also demonstrated various aspects of freshwater aquaculture. The women took active interest in  practicing scientific fish farming. Smt. Narayani Panigrahi (40), a member of that SHG, informed that each of the 11  members got 3 kg fish every time harvesting was done during the year and the rest of the fish were sold to the trader at ` 90/kg. Each household got 12 kg fish for consumption and earned ` 5,566 from sales proceeds. By stocking good  quality fish seed and taking proper care, the productivity level has gone up by 60 per cent as compared to pre-adoption  level. Now the SHG has developed confidence in carp polyculture and interested to undertake fish culture in this pond  with gradual improvement of management practices. Active involvement of poor women in carp polyculture has proven  to be economically beneficial and it is hoped that this would go a long way in strengthening their livelihood.
Keywords: Aquaculture; malnutrition; poverty; polyculture